Francisella tularensis subsp. holarctica DsbA homologue: a thioredoxin-like protein with chaperone function - Schmidt, Monika; Klimentova, Jana; Rehulka, Pavel; Straskova, Adela; Spidlova, Petra; Szotakova, Barbora; Stulik, Jiri; Pavkova, Ivona (Microbiology (Reading, England), 2013)
Francisella tularensis is a highly infectious facultative intracellular bacterium and aetiological agent of tularaemia. The conserved hypothetical lipoprotein with homology to thiol/disulphide oxidoreductase proteins (FtDsbA) is an essential virulence factor in F. tularensis. Its protein sequence has two different domains: the DsbA_Com1_like domain (DSBA), with the highly conserved catalytically active site CXXC and cis-proline residue; and the domain amino-terminal to FKBP-type peptidyl-prolyl isomerases (FKBP_N). To establish the role of both domains in tularaemia infection models, site-directed and deletion mutagenesis affecting the active site (AXXA), the cis-proline (P286T) and the FKBP_N domain (ΔFKBP_N) were performed. The generated mutations led to high attenuation with the ability to induce full or partial host protective immunity. Recombinant protein analysis revealed that the active site CXXC as well as the cis-proline residue and the FKBP_N domain are necessary for correct thiol/disulphide oxidoreductase activity. By contrast, only the DSBA domain (and not the FKBP_N domain) seems to be responsible for the in vitro chaperone activity of the FtDsbA protein.
Keywords: DNA Mutational Analysis; molekulární chaperony; thioredoxiny; Thioredoxins; Virulence; Mutagenesis, Site-Directed; mutantní proteiny; Virulence Factors; sekvenční delece; virulence; Sequence Deletion; mutageneze cílená; Molecular Chaperones; Mutant Proteins; proteindisulfidisomerasy; faktory virulence; Francisella tularensis; mutační analýza DNA; Protein Disulfide-Isomerases